Turnover intention of marketing employees in the leasing industry: Influencing factors - Deva Nita Mulya; Yashinta Putri Dwi Astuti (Institute of Computer Science (IOCS), 2023)
The intention to switch jobs is the desire to resign by employees, influenced by various internal and external factors, and it can have adverse consequences for a company in terms of recruitment costs and providing training to employees. The research background for this study is the intention of an individual in a managerial position (manager) within a company, particularly in the marketing division, which tends to have a relatively high turnover intention compared to other divisions. Therefore, the objective of this research is to analyze the factors influencing the intention to switch jobs among marketing division managers and how both the marketing division managers and the company address this issue. The research method used in this study is qualitative. This research focuses on the factors influencing the desire of marketing manager employees to switch jobs and how the marketing division managers and the company address this desire to switch. Through data collection using interviews, the research found that the desire to switch marketing managers is influenced by organizational commitment factors, which include the material responsibilities that employees must bear when consumers lapse and a lack of support from leadership